PERKEMBANGAN PEREKONOMIAN ISLAM DI BEBERAPA NEGARA DI DUNIA - Musyafah, Aisyah Ayu (Diponegoro Private Law Review, 2019)
ABSTRACT  The Islamic economy is an economic system with the legal basis used is Islamic law. The Islamic economy though uses the basis of Islamic law but this does not deter non-Muslim communities from contributing to the Islamic economic system. Basically Islamic economics has a purpose to prosper, not only to seek profits, so that many countries that do not have the majority of the Muslim community or even liberal countries participate in applying Islamic economics on various sides. Islamic economics applied in various countries which are the prima donnas are Islamic banking or in Indonesia called Sharia Banking. This study aims to find out how the development of Islamic economics in several countries in the world. This research is a normative juridical research with the nature of descriptive research.  Keyword : Islamic Ekonomy, Sharia Banking